2022
DOI: 10.3390/f13122079
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetics of the Orchid Genus Spathoglottis (Orchidaceae: Collabieae) in Peninsular Malaysia and Borneo

Abstract: Phylogenetic relationships of the orchid genus Spathoglottis (Orchidaceae: Collabieae) in Peninsular Malaysia and Borneo were inferred using the internal transcribed spacer of a nuclear ribosomal DNA (nrITS), a plastid gene maturaseK (matK) and the plastid region trnL-F. Eleven species and three infraspecific taxa of Spathoglottis were examined, with two outgroup species, were included in the phylogenetic analysis. The combined plastid and nuclear data revealed Spathoglottis as monophyletic. From the maximum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…ITS-I and ITS-II were genetically divergent between Dendrobium species, as stated in earlier research and it also indicated better taxonomic identification [22,23]. The ITS sequences have been widely used because of their significance in molecular studies of the orchid family [24]. It is a common tool for tracing the evolutionary history of Dendrobium [11,25] and related families across a wide range of taxonomic groups [26,27].…”
Section: Discussionmentioning
confidence: 54%
“…ITS-I and ITS-II were genetically divergent between Dendrobium species, as stated in earlier research and it also indicated better taxonomic identification [22,23]. The ITS sequences have been widely used because of their significance in molecular studies of the orchid family [24]. It is a common tool for tracing the evolutionary history of Dendrobium [11,25] and related families across a wide range of taxonomic groups [26,27].…”
Section: Discussionmentioning
confidence: 54%
“…This study provides the first complete chloroplast genome for the Spathoglottis genus. The data will lead to the availability of omics repositories that can support further systematics, evolutionary, population and conservation research (15). Like most other angiosperm chloroplast, such as Arabidopsis thaliana, S. aurea possessed both cis- and trans-splicing genes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, based on a revision by Chase (7), among the Collabieae tribe the chloroplast genome has been reported for several taxa, such as Calanthe (8)(9)(10)(11) and Tainia (12)(13)(14). Although the group has approximately 450-500 known species, scarce genomic data are available and there are few reports of taxonomic conflicts (9,15,16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations